VCAM1 modulation on endothelial cells – implications for vasculopathy in sickle cell anemia - Silva, Marisa (2020)
Sickle cell anemia (SCA) is a highly heterogeneous and multifactorial-like monogenic disease that arises from homozygosity for the c.20A>T mutation in the HBB gene. Vascular disease is systemic in SCA, with profound effects in organs like the brain, where stroke is the most severe end of the cerebral vasculopathy (CVA) spectrum. Endothelial dysfunction plays a major role in vasculopathy with several adhesion molecules, such as VCAM1, being produced by the endothelium altered as a response to inflammatory cytokine (e.g., TNF-α) signalling. In previous association studies, we found positive associations between the presence of four specific VCAM1 gene promoter haplotypes and i) high blood flow velocities in the median cerebral artery, and ii) a chronic hemolysis biochemical marker. In this study, we aimed to assess the functional role of those VCAM1 promoter haplotypes in endothelial cell response following endothelial activation through TNF-α stimulation. After molecular cloning of 3 haplotype constructs, using a pGL4 promoterless vector, haplotype sequence was confirmed, by Sanger sequencing, prior to transfection. We used EAhy926, HUVEC and HBEC as different endothelial cell models, and performed transfection experiments for each construct, with and without TNF-α stimulation. Differences in promoter activity were assessed by luciferase reporter assay. All haplotypes showed differences in promoter activity, after TNF-α stimulation, in all cell models. Haplotype 1 showed decreased promoter activity, while haplotypes 7 and 8 showed increased activity after TNF-α stimulation, in all cell models. These results are consistent with lower VCAM1 expression due to haplotype 1, and therefore a protective effect. Conversely, a higher expression due to haplotypes 7 and 8, suggests an increased vasculopathy risk, in a pro-inflammatory milieu. The association between specific haplotypes and endothelial cell response further enhances the modifier effect of VCAM1 on endothelial dysfunction and its impact in SCA pathophysiology, as well as its potential role as a biomarker of SCA vasculopathy risk, severity and prognosis.